2015
DOI: 10.1039/c5nr04353k
|View full text |Cite
|
Sign up to set email alerts
|

A dual pH/thermal responsive nanocarrier for combined chemo-thermotherapy based on a copper–doxorubicin complex and gold nanorods

Abstract: The development of treatment protocols that results in a complete response to chemotherapy has been hampered by low efficacy and systemic toxicity. Here, we created a pH sensitive copper-doxorubicin complex within the core of temperature-sensitive liposomes to maintain the stability during blood circulation and trigger Dox release in the tumor site. Synergistically, we also rationally applied gold nanorods (AuNRs) coupled with near-infrared (NIR) field strength to produce a precise and localized temperature, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…TSL + GNR + TSK was significantly different from all other groups. Reproduced with permission . Copyright 2011 American Chemical Society.…”
Section: Nanoparticle‐mediated Cptmentioning
confidence: 99%
See 1 more Smart Citation
“…TSL + GNR + TSK was significantly different from all other groups. Reproduced with permission . Copyright 2011 American Chemical Society.…”
Section: Nanoparticle‐mediated Cptmentioning
confidence: 99%
“…Lei et al developed thermosensitive liposomes based on a copper–Dox complex that were responsive to both pH and heat . Synergistic application of GNRs and dual pH/thermal sensitive liposomes with NIR light produced a precise and localized temperature which remotely controlled Dox release and efficiently inhibited tumor growth.…”
Section: Nanoparticle‐mediated Cptmentioning
confidence: 99%
“…Thus, this limits the combination of PTX and DOX utilizing a remote loading liposomal formulation. It is reported that copper ions (Cu 2+ ) could bind with the anthracene nucleus of DOX to form a stable complex (Cu–DOX), and DOX could be loaded into liposomes using a Cu 2+ gradient 22 , 23 , 24 . Furthermore, there has been reported that the formation of Cu–DOX complexation could induce the death of tumor cells, which is mediated by the generation of reactive oxygen species (ROS), the damage of DNA strand, and lipid peroxidation 25 , 26 , 27 .…”
Section: Introductionmentioning
confidence: 99%
“…An important issue in new DDS is proper release of loaded drug . pH sensitivity of carrier is an applicable feature for cancer therapy, which leads to less harm to normal tissues . The complex of carrier–drug (e.g.…”
Section: Introductionmentioning
confidence: 99%